2014
DOI: 10.1038/ncb3047
|View full text |Cite
|
Sign up to set email alerts
|

Single luminal epithelial progenitors can generate prostate organoids in culture

Abstract: The intrinsic ability to display self-organizing morphogenetic properties in ex vivo culture may represent a general property of tissue stem cells. Here we show that single luminal stem/progenitor cells can generate prostate organoids in a three-dimensional culture system in the absence of stroma. Organoids generated from CARNs (castration-resistant Nkx3.1-expressing cells) or normal prostate epithelium exhibit tissue architecture containing luminal and basal cells, undergo long-term expansion in culture, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
304
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 303 publications
(321 citation statements)
references
References 65 publications
(90 reference statements)
14
304
2
1
Order By: Relevance
“…Hi basal cell 1,000 21 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) Intriguingly, human basal-and luminal-derived tumors demonstrate histologically distinct phenotypes when challenged with the same oncogenes, MYC and AKT1. Tumors derived from basal cells are of a higher grade than tumors derived from luminal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Hi basal cell 1,000 21 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) Intriguingly, human basal-and luminal-derived tumors demonstrate histologically distinct phenotypes when challenged with the same oncogenes, MYC and AKT1. Tumors derived from basal cells are of a higher grade than tumors derived from luminal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been reported that prostaspheres expressed basal cell cytokeratins and P63, the precise placement of prostasphere cells in the overall prostate stem cell lineages and hierarchy has not been reported. Recent reports indicate that prostate organoid cultures contain P-SCs derived from luminal cells (14,15). Together with urogenital mesenchymal cells, both the sphere-and organoid-forming cells can give rise to a glandular structure resembling the prostate in vivo (29).…”
Section: Discussionmentioning
confidence: 99%
“…For organoid culture in hepatocyte medium as described (14), the cells were resuspended in hepatocyte culture medium (designated as Medium H) that consisted of hepatocyte medium supplemented with 10 ng/ml of EGF (PeproTech), 10 m fasudil (Tocris), 1ĎŤ Glutamax (Gibco), 5% Matrigel (Corning), and 5% charcoal-stripped FBS (Gibco) that had been heat inactivated at 55°C for 1 h. Dissociated cells (10,000) were resuspended in Medium H and plated in ultralow attachment 96-well plates (Corning) in the presence of 100 nM dihydroxytesterone. Fresh Medium H (100 l) was added to the wells every other day.…”
Section: Rosa26mentioning
confidence: 99%
See 1 more Smart Citation
“…The in vitro immortalized cell lines usually go through irreversible changes, or crisis, from their original tumors, resulting in loss of tissue specificity, while PDXs do not. It would be very interesting to compare the molecular pathology of human tumors with those of other new experimental systems that do not go through crisis and share histopathology features as in human tumors, such as organoid culture (21,22). If these systems do have similar molecular pathology, they could also function as predictive models, like PDXs.…”
Section: Discussionmentioning
confidence: 99%